Exploring Hidden Narrative Elements through a Close Reading of Vasily Grossman’s Short Story ‘The Life of Il’ya Stepanovich’ (1935) - Ferrandi, Paola (2023)
The subject matter of this paper concerns the early phase of Vasily Grossman’s literary career in the mid-1930s. Prior to this period, the author proved his ability to evaluate the mechanisms of censor-ship and developed his understanding of what was publishable and what could be sanctioned through the publication process of his first novel (Bit-Yunan, Fel’dman 2019). The research materi-al selected for this paper is the lesser-known short story Zhizn’ Il’i Stepanovicha [The life of Il’ya Stepanovich], published in 1935, and the aim is to provide a close reading and an interpretation key to this text. In order to expose the hidden ambiguity of the short story, the chosen research perspec-tive includes a focus on the function of the protagonist as an entity that does not legitimise the so-cialist myth; a narratological approach on the use of proper names, on “perspective” and the role of the narrator with regard to the axiological structure of the text.
Keywords: Grossman, Vasily